Effects of fractional order on performance of fosmc for speed control of PMSM - Mohd Zaihidee, Fardila; Mekhilef, Saad; Marizan, Mubin; Rui, Tang Jing; Mohd Zaihidee, Ezrinda (Penerbit Akademia Baru, 2023)
Fractional order sliding mode control has been applied for speed control of PMSM. However, in many previous works, the effects of the controller's parameters have not been studied. This paper investigates the effects of fractional order on performance of FOSMC speed control of PMSM. In this work, fractional order, α and β of FOSMS-PID were varied, and their performances were compared. The simulation and experimental results show that variation of order of fractional order integration, α and order of fractional order differentiation, β can affect the performance of the FOSMC-PID controller. Selection of α and β values determines balancing strategies between integral and differentiation portion of the controller. Proper value selection and combination of these variables can further contribute to obtain optimum speed tracking, disturbance rejection and chattering reduction abilities.